The Impact of Collaborative Innovation Activities and Innovation Strategy on Innovation Performance in the Telecommunications Industry: Mediating Effects of Knowledge Sharing - Hakim, Derajat Nur; Nasution, Yasmine (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The Indonesian telecommunications industry is developing quickly and competitively, especially in the digital era. Technological developments and market preferences change industry boundaries, so market analysis methods are considered less important and do not provide a solid basis for long-term strategy formulation. Building on knowledge management and innovation capability theory, this study aims to reveal the mechanisms of collaborative innovation processes by investigating the complex relationships between important factors that affect firms' innovation performance in supply chain networks. Using the Structural Equation Model (SEM) method, the survey of 100 Unit Leaders Respondents in Indonesian Telecommunications companies showed a significant positive relationship between collaborative innovation activities, knowledge sharing, innovation strategy, and company innovation performance. In addition, it is expected that knowledge sharing plays a partial mediating role in the relationship between collaborative innovation activities and firm innovation performance. The innovation strategy moderately affects collaborative innovation activities about innovation performance. These results contribute to collaborative innovation process management by offering a nuanced conceptualization of collaborative innovation - the relationship between innovation performance between units within Indonesia's largest telecommunications company.